A novel deep learning model for detection of denial of service attacks in HTTP traffic over internet. (8th April 2020) - Punitha, V.; Mala, C.; Rajagopalan, Narendran
The technological advancements in internet and mobile communications bring new dimension to the usage of internet applications and services. The accessibility to the enhanced services is intentionally blocked by the denial of service attacks. This paper proposes a novel deep learning classification model to detect the denial of service attacks in application layer for different network environments, such as wired network, ad hoc network and mobile ad hoc network. The simulation results illustrate that the performance of the proposed deep learning model is proficiently improved compared to existing bio-inspired and machine learning models in terms of detection accuracy and classification metrics.